Upaya Meningkatkan Hasil Belajar Seni Budaya Melalui Model Pembelajaran Mind Mapping - Kasmin, Kasmin (JURNAL PENA EDUKASI, 2018)
Abstract: This researcher is done with the aim to know the improvement of learning result of student history through Mind Mapping learning model. Subjects in this study were students of class IX.6 with a total of 36 students. The instrument used is a test in the form of a matter of reflection. the instrument used is a test in the form of multiple problems. The results obtained on the initial test there are 10 complete students (classical completeness 27.78%) with an average test score of 55.83 with low ability category. After the cycle 1 of the results of the test cycle 1 total number of students who completed there are 20 students (55.56% classical completeness) with average test scores 68.06 medium category. In cycle 2 of test result of cycle 2, there were 31 students who have obtained learning completeness (75%) with average test score of 75 high category. Thus it can be concluded that Mind Mapping strategy can improve the learning result of Art Art Culture of Pure Fine Art of Nusantara in Class IX.6 SMP Negeri 1 Kisaran academic year 2016/2017. Keywords: mind mapping, Fine Art Nusantara Abstrak: Peneliti ini dilakukan dengan tujuan mengetahui peningkatan hasil belajar Sejarah siswa melalui model pembelajaran Mind Mapping. Subjek dalam penelitian ini adalah siswa kelas IX.6 dengan jumlah 36 orang siswa. Instrumen yang digunakan adalah tes yang berupa soal refleksi. intrument yang digunakan adalah tes yang berupa soal berganda. Hasil penelitian diperoleh pada tes awal terdapat 10 orang siswa yang tuntas (ketuntasan klasikal 27,78%) dengan rata-rata nilai tes 55,83 dengan kategori kemampuan rendah. Setelah dilakukan siklus 1 dari hasil tes siklus 1 jumlah siswa yang tuntas ada 20 siswa (ketuntasan klasikal 55,56%) dengan rata-rata nilai tes 68,06 kategori sedang. Pada siklus 2 dari hasil tes siklus 2 terdapat 31 siswa yang telah memperoleh ketuntasan belajar (75%) dengan rata-rata nilai tes 75 kategori tinggi. Dengan demikian dapat disimpulkan bahwa strategi Mind Mapping dapat meningkatkan hasil belajar Seni Budaya Materi Seni Rupa Murni Nusantara di Kelas IX.6 SMP Negeri 1 Kisaran Tahun Pelajaran 2016/2017. Kata kunci: mind mapping, reni rupa murni nusantara